Safety and Effectiveness of Outpatient Parenteral Antimicrobial Therapy (OPAT) in the Aged Population. (4th October 2017) - Van Anglen, Lucinda J; Mandel, Richard M; Nathan, Ramesh V; Krinsky, Andrew H; Luu, Quyen; Bacon, Alfred E; Baker, H Barry; Schroeder, Claudia P; Couch, Kimberly A
Abstract: Background: The aged population (≥75 years) have multiple comorbidities and are at increased risk of adverse events associated with intravenous antimicrobial therapy. Hospitalization (hosp) occurs frequently. This group presents challenges for site of care and reimbursement, which may be met with provision of OPAT through a physician office infusion center (POIC). This setting allows treatment immediately following hosp or directly from the community, thus avoiding hosp. For the aged patient (pt) population, we evaluated safety and effectiveness of OPAT in a POIC. Methods: Records from 13 POICs were queried for patients ≥75 years receiving OPAT courses from January to July 2016. Data included demographics, therapy, disease characteristics, effectiveness and safety. Effectiveness was assessed as completion of therapy and no unplanned hosp related to the underlying infection. Safety assessment included adverse drug reactions (ADRs), catheter complications (CC) and hosp admissions for causes other than those related to the underlying infection. Descriptive statistics and regression analyses were performed. Results: There were 260 OPAT patient courses provided. Mean age was 81 ± 5 years, 64% male. 51% were treated directly from the community and 49% post hosp. The most common infections were bone and joint (32%), genitourinary (21%), skin and skin structure (20%) and respiratory (12%). OPAT met criteria for effectiveness in 95%, with 247/260 completing therapy and avoiding infection-related hosp. Antimicrobials most frequently used were vancomycin ( n = 59), ceftriaxone ( n = 43), cefepime ( n = 35) and ertapenem ( n = 32). Median length of OPAT was 14 days (range 1–79). OPAT was assessed as safe in 81% of patients (211/260). 49 patients reported ≥1 safety events including ADRs (40; 15%), CC (6; 2.3%), and hosp (17; 6.5%). 9 hosp patients completed OPAT following discharge. Most common ADRs were diarrhea ( n = 9), fatigue ( n = 9) and nausea ( n = 8) with 4 hosp for serious ADRs. All CCs resolved and there were no mortalities. Significant risk factors associated with safety events were drug allergies (OR=2.47, CI=1.31–4.65, P = 0.005), ≥3 comorbidities (OR=3.92, CI=1.16–13.23, P = 0.027) and hypertension (OR=2.19, CI=1.04–4.64 P = 0.039). Conclusion: Provision of OPAT through a POIC demonstrated to be exceptionally safe and effective in the aged population. Disclosures: L. J. Van Anglen, Theravance: Scientific Advisor, Consulting fee R. V. Nathan, Merck: Speaker's Bureau, Speaker honorarium Allergan: Speaker's Bureau, Speaker honorarium The Medicines Company: Speaker's Bureau, Speaker honorarium K. A. Couch, Merck: Speaker's Bureau, Speaker honorarium Allergan: Speaker's Bureau, Speaker honorarium